The mixed blessing of labour shortage: German overemployment in the 1960's - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
In German post-war historiography, the 1960s are usually viewed as a time of political and economic transition. Politically, the period marks the watershed between the paternalistic conservatism of the Adenauer era and the full-scale social democracy of the early seventies, with the so-called 'grand coalition' government of the late sixties being the tangible incarnation of transition. Economically, the period figures as a bridge between the German miracle of the fifties and the slow-down and stagnation of the seventies and eighties, with national income growing at a rate which was still remarkably high by historical standards, but not more than average by the international standards of the time. In one respect, however, the 1960s do unambiguously figure as a peak of German history after World War II and even in this century, namely in terms of labour shortage.
Keywords: 330; Arbeitsmarkt; Vollbeschäftigung; Deutschland